Reshaping cyclist mobility: Understanding the impact of autonomous vehicles on urban bicycle users - Alexander Gaio; Federico Cugurullo (Journal of Cycling and Micromobility Research)
Autonomous Vehicles (AVs) present a jarring new normal for negotiation on public streets. Current communication and interaction stand to be disrupted with the presence of AVs. Active transport users, specifically bicycle users, rely on human communication and subtle cues to feel confident when negotiating with other road users. Shifts in communicability with AVs presents a unique challenge for bicycle users. It remains unclear how AVs will impact urban bicycle users. This paper employs a mixed-methods approach to understanding impacts that AVs have on urban bicycle users in four test sites with varying levels of traffic stress. Interviews and focus groups were used across different traffic stress scenarios in three countries to understand how bicycle users will be impacted by AVs in real-world scenarios. The results represent a pioneering cross-section of four bicycle cultures’ exposure to AVs. Results universally show that, compared to conventionally operated vehicles, an enduring sense of unease remains unresolved with AVs and that shifting focus to bicycle user experiences and prioritizing the needs of a diverse population of non-occupants will be critical. If AVs are not deployed responsibly and responsively, they could turn bicycle users away from cycling in a streetscape where active transport users are already marginalized.